Assessing student Engagement in School: Development and validation of a four-dimensional scale - Veiga, Feliciano Henriques (2016)
This study is a product of the project PTDC/CPE-CED/114362/2009 – Student Engagement in School: Differentiation and Promotion, financed by national funding through The Foundation for Science and Technology (FCT) from Portugal.